(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: The most prevalent cyanotic congenital cardiac condition is the tetralogy of Fallot (TOF). A congenital heart defect is a flaw in the structure of the heart that is present at birth. The normal flow of blood through the heart is disrupted by this type of cardiac defect. It accounts for about 6% to 10% of all congenital heart defects. The congenital heart condition double outlet right ventricle (DORV) occurs when two blood arteries do not attach to the heart. It can affect 1 to 3% of people with congenital cardiac disease. Case Presentation: A newborn male child was brought by her parents to the paediatric ward with a chief complaint of shortness of breath, cyanosis, hypoglycaemia, and convulsion. In the case of Tetralogy of Fallot with Double outlet right ventricle. The primary therapeutic interventions were given to the newborn patient and he was treated with antibiotics and vasodilators. Conclusion: The newborn male old child with complaints of shortness of breath, cyanosis, hypoglycaemia, and convulsion and diagnosed with tetralogy of Fallot with double outlet right ventricles. After the proper therapeutic interventions and treatment, the client’s condition is improved. He has been able to maintain oxygen saturation up to 88-94% and reduced hypoglycaemia and convulsion, cyanosis.